1989
DOI: 10.1063/1.101752
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of acceptors in InP resulting from CH4/H2 reactive ion etching

Abstract: Articles you may be interested inDependence of selectivity on plasma conditions in selective etching in submicrometer pitch grating on InP surface by CH4/H2 reactive ion etching J. Appl. Phys. 109, 073516 (2011); 10.1063/1.3573536 X-ray photoelectron spectroscopy damage characterization of reactively ion etched InP in CH 4 -H 2 plasmas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…The reduction and/or removal of these oxides by means of atomic hydrogen cleaning have been shown to unpin the Fermi level (40,41) and reduce interface defect density (42). Another key feature of atomic hydrogen is its ability to passivate native defects within the semiconductor (23,30,43). This attribute has also been exploited in GaN and GaAs to recover damage arising from dry etch processing through the passivation of etch-induced defects (44,45).…”
Section: Dry Etch Process Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction and/or removal of these oxides by means of atomic hydrogen cleaning have been shown to unpin the Fermi level (40,41) and reduce interface defect density (42). Another key feature of atomic hydrogen is its ability to passivate native defects within the semiconductor (23,30,43). This attribute has also been exploited in GaN and GaAs to recover damage arising from dry etch processing through the passivation of etch-induced defects (44,45).…”
Section: Dry Etch Process Optimizationmentioning
confidence: 99%
“…(14,(16)(17)(18)(19)(21)(22)(23)(24)(25)(30)(31)(32)(33) have been used to yield structural, chemical and electrical information relating to etch-induced damage. Our concern here is the extent of electrical damage to the dielectric/sidewall interface.…”
Section: Sidewall Damage Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma processes like reactive ion etching use gaseous mixtures that often include H2 and are an obvious source of atomic hydrogen [87,88]. It has also been demonstrated that hydrogen can be introduced during benign processes like polishing, wet etching [76,77], or annealing in forming gas [83].…”
Section: Unintentional Dopant Passivationmentioning
confidence: 99%
“…Research has been conducted on the physical damage and hydrogenation effects during RF' plasma exposure (1,2) and epitaxial growth (3, 4) in the 111-V material system. Device consequences of this damage or chemical alteration have received less attention, particularly in active light emitting devices.…”
Section: Introductionmentioning
confidence: 99%